2015
DOI: 10.1515/amm-2015-0151
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Nickel On The Microstructure And The Mechanical Properties Of Sn-0.7Cu Lead-Free Solders

Abstract: This paper investigates the effects of small amount nickel addition (0, 200, 400, 800, 1800 ppm) on the microstructure and the mechanical properties of Sn-0.7Cu lead-free solder alloys. It is known that even ppm level Ni additions have significant effects on the microstructure of Sn-Cu solder alloys. Ni suppresses the growth of β-Sn dendrites in favour of eutectic formation. As the nickel content increases, the microstructure undergoes a morphological evolution from hypoeutectic through fully eutectic to hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Similar microhardness ($11.96 HV) of Sn-0.7Cu alloy was reported by Mohd Salleh et al (2012). However, a slightly lower microhardness (<12 HV) of bulk Sn-0.7Cu alloy has also been reported by other researchers (Gyenes et al, 2015;Zhao et al, 2019). A slight increment in hardness, i.e.…”
Section: Microhardnesssupporting
confidence: 84%
“…Similar microhardness ($11.96 HV) of Sn-0.7Cu alloy was reported by Mohd Salleh et al (2012). However, a slightly lower microhardness (<12 HV) of bulk Sn-0.7Cu alloy has also been reported by other researchers (Gyenes et al, 2015;Zhao et al, 2019). A slight increment in hardness, i.e.…”
Section: Microhardnesssupporting
confidence: 84%
“…Owing to the larger tip size of the Vickers method (200 nm), a higher load is commonly needed (Cagliero and Maizza, 2011). Recent measurements involved loading values such as 25 g (Negm et al, 2010), 100 g (Chen et al, 2016b), 300 g (Hu et al, 2013, Gyenes et al, 2015 and 10 gf (Chen et al, 2012). Additionally, a shorter dwell time (10-20 s) was sufficient for the indentation, as the lead-free solders were easily deformed (Chen et al, 2012;Tsao et al, 2016).…”
Section: Vickers Hardness Testmentioning
confidence: 99%
“…The approach of characterizing lead-free solders in the bulk form is practical for certain research studies which involve (Tsao et al, 2016;Gyenes et al, 2015) the following:…”
Section: Hardness Of Bulk Solder Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect 0.08 wt.% Ni-addition on the microstructure and the mechanical properties of Sn-0.7 Cu alloy has been studied by Gyenes et. al [16]. They found that Sn-0.7 Cu-Ni alloy becomes fully eutectic [β-Sn + (Cu,Ni) 6 Sn 5 ], and the ultimate tensile strength (UTS), yield strength (YS) and hardness (HV) were increased.…”
Section: Introductionmentioning
confidence: 99%